A Conspectus of the Functions of the Judiciary under the Zimbabwe Constitution 2013. Issue 2 (May 2017) - Chitimira, Howard
Abstract : This article provides an overview analysis of the relevant provisions of the Zimbabwe Constitution Amendment Act 20 of 2013 (Zimbabwe Constitution 2013) that, inter alia, deals with the functions of the judiciary. To this end, the article examines the adequacy of the aforesaid provisions in relation to their practical enforcement and the promotion of constitutional democracy in Zimbabwe. In light of this, a synoptical analysis of the gaps and flaws of the provisions dealing with the functions of the judiciary under the Zimbabwe Constitution 2013 will be provided. In addition and where applicable, a comparative analysis of these provisions and those that were provided under the Lancaster House Constitution of Zimbabwe Amendment Act 19 of 2008 (Lancaster House Constitution 2008) will be undertaken. This is done to explore whether the flaws and gaps that were associated with the relevant provisions of the Lancaster House Constitution 2008 are now corrected under the Zimbabwe Constitution 2013. Thereafter, possible recommendations and concluding remarks will be stated.